Zakat Fatwa in the Digital Economy: Reaffirming Maqāṣid Al-Sharī‘ah Within the SDGs Framework - Ryan Bianda; Ahmad Nuh; Adam Sugiarto; Kalfajrin Kurniaji (Universitas Muhammadiyah Surakarta, 2026)
Objective: This study aims to examine how the 2024 Majelis Ulama Indonesia (MUI) fatwa on zakat for YouTubers, influencers, and other digital creative workers reconstructs Islamic legal reasoning in response to the expanding digital economy while contributing to the Sustainable Development Goals (SDGs). Theoretical framework: The study is grounded in the theoretical framework of maqāṣid al-Sharīʿah, Islamic social finance, socio-legal theory, and regulatory governance, positioning fatwa as a dynamic legal instrument that integrates religious values with contemporary socio-economic realities. Literature review: Existing studies have extensively discussed professional zakat, Islamic philanthropy, and digital economic transformation; however, limited attention has been given to the socio-legal implications of digital zakat fatwas and their relationship with sustainable development. Method: Employing a qualitative socio-legal research design, the study combines normative juridical and sociological approaches through documentary analysis of the 2024 MUI fatwa and relevant literature on Islamic economic law, Islamic social finance, and digital governance. Results: The findings demonstrate that the fatwa contextualizes classical income zakat principles by recognizing digital professions as legitimate zakatable occupations based on lawful earnings and ethical content creation. This legal adaptation expands the resource base of Islamic social finance, enhances financial inclusion, and reinforces contributions to poverty alleviation, decent work, reduced inequalities, and accountable institutions in line with the SDGs. Furthermore, the analysis reveals that digital zakat functions as an ethical governance mechanism linking theology, public policy, and financial technology while embedding maqāṣid-oriented values into emerging digital business ecosystems. Implications: The study implies that adaptive Islamic legal interpretation can strengthen sustainable economic governance in rapidly evolving digital societies. Novelty: Its novelty lies in conceptualizing the digital zakat fatwa not merely as a doctrinal religious opinion but as an innovative socio-legal regulatory framework that advances faith-based sustainability, ethical digital entrepreneurship, and institutional transformation within the contemporary Islamic digital economy.